2011
DOI: 10.5012/bkcs.2011.32.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Direct Adsorption and Molecular Self-Assembly of Octylthioacetates on Au(111) in the Vapor Phase

Abstract: Self-assembled monolayers (SAMs) are a very promising construct for monomolecular thin films with various practical applications because they are very amenable to surface modification and functionalization of metal surfaces.1-6 Alkanethiol SAMs on gold surfaces have been thoroughly studied by a number of research groups, and their structural properties have been well characterized. Organic thiols are prone to easily oxidize to disulfides or other oxidized species that can affect the formation and structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Organic thiols are the best model compounds because they spontaneously form closely packed SAMs with a molecularly controllable thickness on gold surfaces via the formation of S–Au chemical bonds. ,,, SAMs of alkanethiols with a normal alkyl chain at saturation coverage on gold have particularly well-ordered domains with a hexagonally packed (√3 × √3)­R30° or c (4 × 2) structure. ,,,,, However, a drawback of using thiols for SAM preparation is that they can readily be oxidized to other oxidized species in the solution, resulting in undesirable structural defects and inhomogeneous interface structures in SAMs. , Therefore, new molecular assemblies on metals have been developed using S-containing alternatives having high chemical stability in solution or air such as organic thioacetates, , thiosulfates, thiocyanates, and sulfenyl chlorides . Direct adsorption of organic thioacetates on gold in the solution led to the formation of less ordered SAMs, , , whereas more ordered SAMs could be prepared via in situ deprotection of acetyl groups using specific deprotection reagents. , Other alternatives on gold showed similar structural behaviors: they usually form SAMs with inferior structural quality compared to the analogue thiols, but the structural quality of these SAMs was enhanced significantly using optimized SAM preparation conditions. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic thiols are the best model compounds because they spontaneously form closely packed SAMs with a molecularly controllable thickness on gold surfaces via the formation of S–Au chemical bonds. ,,, SAMs of alkanethiols with a normal alkyl chain at saturation coverage on gold have particularly well-ordered domains with a hexagonally packed (√3 × √3)­R30° or c (4 × 2) structure. ,,,,, However, a drawback of using thiols for SAM preparation is that they can readily be oxidized to other oxidized species in the solution, resulting in undesirable structural defects and inhomogeneous interface structures in SAMs. , Therefore, new molecular assemblies on metals have been developed using S-containing alternatives having high chemical stability in solution or air such as organic thioacetates, , thiosulfates, thiocyanates, and sulfenyl chlorides . Direct adsorption of organic thioacetates on gold in the solution led to the formation of less ordered SAMs, , , whereas more ordered SAMs could be prepared via in situ deprotection of acetyl groups using specific deprotection reagents. , Other alternatives on gold showed similar structural behaviors: they usually form SAMs with inferior structural quality compared to the analogue thiols, but the structural quality of these SAMs was enhanced significantly using optimized SAM preparation conditions. …”
Section: Introductionmentioning
confidence: 99%
“…Organic selenocyanates could be also a strong alternative to prepare selenolate SAMs because they are chemically more stable than selenols. However, there have been only limited reports regarding the adsorption of organic selenocyanates on Au and Ag nanoparticles , and their SAM formation on Au(111) surfaces in solution. , Moreover, STM observations showed that the adsorption of organic selenocyanates on Au(111) in a 1 mM ethanol solution at room temperature (RT) led to the formation of poorly ordered selenolate SAMs, whereas SAMs formed at high temperature were composed of mixed disordered and ordered domains. , In contrast to alkanethiol SAMs, the deposition method strongly affects the adsorption behavior and structural order of SAMs on Au(111) formed from acetyl-protected thiols or organic thiocyanates. , Organic thiocyanate SAMs on Au(111) with long-range ordered domains and a homogeneous interface can be prepared using ambient-pressure vapor deposition (hereafter, simply referred to as vapor deposition) compared with solution deposition. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation